(untitled) (JAKPP (Jurnal Analisis Kebijakan & Pelayanan Publik), 2022)
Local governments implement e-government programs as a form of bureaucratic reform to achieve good governance. However, the implementation of E-government in South Halmahera Regency, geographically an archipelagic area, has its challenges, which the authors make as problems in this study. To assist research analysis using e-government theory. This research is qualitative research with a descriptive approach to analyzing the N-VIVO 12 Plus software. Based on the findings, the South Halmahera district has implemented e-government to a low degree with various challenges, including the distribution of telecommunications technology network infrastructure is not evenly distributed, limited budget support, lack of telecommunications infrastructure, lack of skilled resources, limited supply of electricity networks, lack of training and knowledge transformation of the apparatus, limited public knowledge, low socialization of e-government programs, not maximal collaboration and synergy between stakeholders. In implementing e-government, it is considered to have benefits, while to encourage the strengthening of e-government implementation, the South Halmahera government has planned the Labuha Smart City.